Possible obesogenic effects of bisphenols accumulation in the human brain - Charisiadis, Pantelis; Andrianou, Xanthi; Van Der Meer, Thomas P.; Den Dunnen, Wilfred F. A.; Swaab, Dick F.; Wolffenbuttel, Bruce H. R.; Makris, Konstantinos C.; Van Vliet-Ostaptchouk, Jana V. (My University, 2018)
Evidence of bisphenols’ obesogenic efects on humans is mixed and inconsistent. We aimed to explore the presence of bisphenol A (BPA), bisphenol F (BPF) and chlorinated BPA (ClBPA), collectively called the bisphenols, in diferent brain regions and their association with obesity using post-mortem hypothalamic and white matter brain material from twelve pairs of obese (body mass index (BMI) >30kg/m2) and normal-weight individuals (BMI <25kg/m2). Mean ratios of hypothalamus:white matter for BPA, BPF and ClBPA were 1.5, 0.92, 0.95, respectively, suggesting no preferential accumulation of the bisphenols in the grey matter (hypothalamic) or white matter-enriched brain areas. We observed diferences in hypothalamic concentrations among the bisphenols, with highest median level detected for ClBPA (median: 2.4ng/g), followed by BPF (2.2ng/g) and BPA (1.2ng/g); similar ranking was observed for the white matter samples (median for: ClBPA-2.5ng/g, BPF-2.3ng/g, and BPA1.0ng/g). Furthermore, all bisphenol concentrations, except for white-matter BPF were associated with obesity (p<0.05). This is the frst study reporting the presence of bisphenols in two distinct regions of the human brain. Bisphenols accumulation in the white matter-enriched brain tissue could signify that they are able to cross the blood-brain barrier.
Keywords: Bisphenol A; Bisphenol F; Chlorinated BPA; Bisphenols